Nurse coordinator leadership and work environment conflicts: consequences for physical and work-related health of nursing staff - Sili, Alessandro; Fida, Roberta; Trezza, T.; Vellone, E.; Alvaro, Rosaria (La Medicina del Lavoro, 2014)
Background: Research has amply demonstrated that positive leadership counters the onset of burnout and conflicting situations between colleagues that in turn create favourable conditions for a healthy organization and consequently for good quality of care. Objectives: To investigate if more positive leadership is associated with lower levels of conflict in the work environment that in turn are associated with lower levels of burnout, psychosomatic disorders and negative indicators of work environment (feeling not being adequately appreciated, lack of clarity about tasks and roles, gossip, resentment towards the organization), and with higher levels of work satisfaction. Method: Five scales of QISO (Nursing Organizational Health Questionnaire) and the Maslach Inventory (Burnout scale), were administered to a total of 192 nurses working in medical and surgical departments of two different Italian hospitals. The study design was cross-sectional. To test the hypothesis a structural equation model (SEM) was used. Results: The results of this study demonstrate the crucial role played by positive leadership of nursing coordinators that, directly and indirectly, promotes a healthy work environment with lower conflicts, burnout, and psychosomatic disorders among nurses and limits the presence of negative indicators in workplace. Conclusion: This study demonstrates the key role of the nursing coordinator in creating a healthy work environment that contributes to physical and work-related health of the nursing staff.